Relationship among self-concept, locus of control, motivation and mathematics achievement of upper basic school students (2013)
The study examined the relationship among self-concept locus of control, motivation and mathematics’ achievement among upper Basic school students in Oyo and Osun State of Nigeria. Three hundred students comparises male and female were randomly selected from ten schools in the two states constituted the sample for the study. SCLOCM was used to collect data with cronbach alpha (a = 087) and standardized mathematics achievement test, Two research questions were raised and answered in the study using multiple regression and analysis of variance. The results of the findings indicates the following; that a significant relationship exists among self-concept, locus of control, motivation and mathematics achievement, that these variables when taken together predicts students mathematics achievement. Implication of this finding for school administrators, mathematics teachers stakeholders and government were proferred.